(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This article reports on a study which explored teachers re-conceptualization and re-orientation process during their in-service training for ICT-pedagogy integration in teaching and learning. The qualitative research design was used for the study. It was found that there was a limited ICT infrastructure as well as inadequate technological access and reliability, the participating teachers were engaged in authentic hands-on learning experience and that the teachers engagement in the learning activities demonstrated they had not developed expertise in ICT usage for teaching and learning. It was therefore recommended that opportunities to acquire professional ICT integration skills for both teachers and trainers be expanded.